Social media reliance in organization: choosing the right medium to enhance job performance / Ahlam Abdul Aziz, Shazleen Mohamed and Khairul Azman Abdul Rashid - Abdul Aziz, Ahlam; Mohamed, Shazleen; Abdul Rashid, Khairul Azman (UiTM Cawangan Negeri Sembilan, 2022)
Social media has become popular for communication, interaction and knowledge sharing on the internet. Most of the industry uses social media as a medium of communication to interact with people in order to fulfil number of purposes such as work and personal matter, including the workplace as well. Reliance on social media has played an important role from the moment it been introduced, allowing connections to be made throughout the world, given the increasing level of interaction and socialization in the lives of various groups. This study aims to describe social media as popular medium among employees to communicate among themselves. Social media now is changing the methods of social connectivity and a part of important aspect to improve employees job performance. It also highlighted how organization adapted social media in their workplace as the right medium to communicate in helping them with their daily routine in organization and working environment. This study also looked into the reason why some individual depends on social media as their channel to communicate among the colleagues within the organization. Study found that WhatsApp is the most chosen medium as a platform to increase job performance in organization. The dependence of social media in organization related to the usage as medium to communicate. It has also identified the factors that encourage users to choose it as medium in organization. It is important to identify the reasons of choosing the right tools, as it is important for the organization to get benefit from the usage or choosing the selected channel or medium to communicate.